ENGLISH SHORTENINGS DENOTING THE NOTION OF ‘A HUMAN BEING’ - Begizova Madina Karimovna (Western European Studies, 2024)
The article is devoted to the study of the structural features of abbreviations denoting the concept of ‘а human being’. Analysis of lexicographic material revealed a certain variety of types of models according to which the targeted group of lexical units is formed. However, three stood out as the most representative. These are: abbreviations, represented by the initial part of words, abbreviations of combinations, which are represented by the initial letter of each component, and abbreviations of word combinations in which the first element is retained in its entirety, while the remaining elements are usually abbreviated up to the initial letter.
Keywords: abbreviation; apheresis; acronym